Postoperative Analgesia with Epidural Dexmedetomidine Compared with Clonidine following Total Abdominal Hysterectomies: A Prospective Double-blind Randomized Trial - Chiruvella, Sunil (Anesth Essays Res, 2018)
BACKGROUND AND AIMS: Anesthesia for total abdominal hysterectomies is not only concerned with relieving pain during intraoperative period but also during the postoperative period. We compared clonidine and dexmedetomidine as an adjuvant to levobupivacaine for epidural analgesia with respect to onset and duration of sensory block, duration of analgesia, and adverse effects. MATERIALS AND METHODS: A total of 80 individuals between the age of 45 and 65 years of American Society of Anesthesiologists (ASA) physical status Classes I and II who underwent total abdominal hysterectomies were randomly allocated into two groups, comprising 40 patients in each group. Group LC received 10 ml of 0.125% levobupivacaine and 2 μg/kg of clonidine while Group LD received 10 ml of 0.125% levobupivacaine and 1 μg/kg of dexmedetomidine through the epidural catheter. Onset of analgesia, time of peak effect, duration of analgesia, cardiorespiratory parameters, side effects, and need of rescue intravenous (IV) analgesics were observed. The data analysis was carried out with Z-test and Chi-square test. RESULTS: The demographic profile and ASA physical classes were comparable between the groups. Group LD had early onset, early peak effect, prolonged duration, and stable cardiorespiratory parameters when compared with Group LC. Less number of patients (42.5%) in Group LD required IV rescue analgesics when compared to Group LC (70%) and was statistically significant. The side effects’ profile was also comparable. CONCLUSION: Dexmedetomidine is a better neuraxial adjuvant compared with clonidine for providing early onset and prolonged postoperative analgesia and stable cardiorespiratory parameters.